In-season training load variation - heart rate recovery, perceived recovery status, and performance in elite male water polo players: a pilot study - Botonis, P. G.; Arsoniadis, G. G.; Smilios, I.; Toubekis, A. G. (Sports Health: A Multidisciplinary Approach, 2025)
Background Increased training and competition demands of the in-season period may disturb athlete fatigue and recovery balance. The aim of this study was to describe the training load distribution applied in a competitive period and the training adaptations and fatigue/recovery status of elite water polo players.